(untitled) (International Journal of Physiotherapy, 2016)
Background: Cervical pain is a common condition and almost two thirds of population suffers with this condition. Cervical region is the commonest region for non-traumatic neck pain. Neck pain generates many muscular disturbances in the neck region and may result in tightness of muscles of cervical region. Stretching is considered as an effective mean of treating cervical pain. Isometric exercise is used to enhance the performance of muscles because it provides strength required to perform dynamic exercise. Both of the regimens either separately or combined are used in clinical settings to treat nonspecific cervical pain. This study aims to compare the results of cervical isometrics with and without stretching exercises in reducing non-specific cervical pain Methods: A randomized controlled trial research was performed at physiotherapy department of Mayo Hospital Lahore, Pakistan. A convenience sample of 40 participants was divided into two groups. The cervical isometric exercise was applied to group A and stretching plus isometric exercise to group B for 3 weeks. Nonspecific neck pain was analyzed by using visual analogue scale and goniometry for pre and post treatment assessment. Results: Isometric exercises play an effective role in relieving pain (p value is 0.03) and minimizing inability of the body to perform functional activities (p value is 0.004) in contrast to the patients of group A. Isometric exercises were applied to the patients of group A (Level of pain: pain value is 0.172) and (physical inability to perform functional activities has P value 0.201). Conclusion: The result showed that the patients with the complain of non-specific neck discomfort who were treated by cervical isometric alone, showed less improvement in pain relief in contrast to the patients who were treated by the cervical isometric long with stretching.